Academic perception of analysis about the environment and conservation of water resources in the municipality of Missão Velha-CE - Melo, Nyrreyne Dias Pereira de; Santos Filho, Edilson Bezerra dos; Melo, Arysa Dias Pereira de; Generino, Maria Elizete Machado (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The research aimed to evaluate the perceptions of students of Biology programs related to environment and water resources used in the municipality of Missão Velha – CE in order to promote environmental awareness. This was a quantitative study with content analysis and as a data collection procedure we used a semi-structured questionnaire as a research tool. The results expressed that knowledge and interest in the subject are relevant environment, one of the problems emphasized was the absence of basic sanitation, only a small number of students participating in activities aimed at conservation of natural resources. It is imperative that directed the Environmental education activities are stimulated to better preservation of natural resources.